The Ever-growing China’s Maritime Rise and South China Sea Dispute: A Literature Review - Heriawan - (Universitas Airlangga, 2022)
This article explores the implication of China’s increasing maritime capability and what its means for the world peace. Is China’s maritime expansion a threat or a peaceful one? In this article, the author scrutinies the recent debates and its problematic interpretation of China’s maritime rise through the perspective of integrative review and neoclassical realism approach. First, this article describes the concept of rising power in International Relations and provide an overview of South China Sea (SCS) dispute state-of-the-conflict. Second, it would provide a thorough discussion of the China’s behaviour and intention in the disputed sea. The discussion extends over several prominent concepts: Rising Power, Global & Regional Order, Strategic Orientation, and National Conception. To conclude, this article argues the ever-expanding China maritime strength has given advantages to China’s claim in the disputed sea. China’s strategy pushing the limit of aggressiveness under the threshold of war. At the same time reassuring other countries through various cooperative and economical means.